Carpal Tunnel Syndrome – etiology and diagnostics - Ciechanowska, Katarzyna; Łukowicz, Małgorzata (Journal of Education, Health and Sport, 2017)
The carpal tunnel syndrome (CTS) is one of the most frequent peripheral neuropathies of the upper extremities, caused by increasing pressure in the carpal tunnel or a decrease in its volume, which leads to compression and disturbances in blood supply to the median nerve. This condition significantly affects quality of life, limiting manual dexterity and the ability to perform daily activities. Thus, social needs dictate finding effective treatment methods for CTS.